MUDIK LEBARAN: STUDI KUALITATIF - Bambang Bemby Soebyakto (Jurnal Ekonomi Pembangunan, 2011)
This study analyze the behavior of the community and benefit from the Mudik. Where research is qualitative by incidental sampling method that is getting "informants" or respondent found their place immediately. The travelers can be met at the railway station, harbor boats, airports and intercity bus terminal - across the province. Social situation or informants in this study amounted to 196 people. Mudik Lebaran can be categorized as circular migration because it is temporary and in a short time. Activities result in significant benefit, especially the annual income for a particular area, especially when people from the area many migrate to big cities. Cyclical revenue turnover occurs by travelers for their homeland. Revenue can be directly from the expenditure incurred by nomads - travelers of handicrafts goods whether by food or other goods. The transportation received no small amount of revenue due to the Lebaran transport increased rates are usually quite large, including other costs. This can be regarded as an annual contribution of relatively of relatively large. Keywords: Musik Lebaran, Income, expenses, transportation equipment